RANCANG BANGUN ALAT PENGERING KERUPUK RAMBAK IKAN LAUT DI KUBE SARI ENAK WOTGALEH SUKOHARJO - Darsini Darsini; Suprapto Suprapto; Budi Wibowo (Injection: Indonesian Journal of Vocational Mechanical Engineering, 2023)
The Sukoharjo sub-district is one of the sub-districts in the city center, but the income of the population who are farm laborers reaches 1,485 people, and the others reach 1,883 people. In this village there are also 44 small industries engaged in the production of snacks. One of these small industries has formed a joint business group called KUBE "Sari Enak" which is currently still growing. This research was carried out by applying a dryer application aiming to provide an appropriate technology that is easy, cheap and efficient for the community. The method used in the application of this tool is the application of a rambak dryer and the provision of materials/theories regarding the technology of the rambak dryer. The results of community service activities in the form of this dryer application can save processing time in the process of drying sea fish crackers.